Pledge-and-Review Bargaining - Bård Harstad (Center for Economic Studies and ifo Institute (CESifo), 2018)
Real-world negotiations differ fundamentally from existing bargaining theory. Inspired by the Paris Agreement on climate change, this paper develops a novel bargaining game in which each party quanti.es its own contribution (to a public good, for example), before the set of pledges must be accepted. I first show that, if the tolerance for delay is uncertain, each equilibrium pledge coincides with an asymmetric Nash bargaining solution. The weights placed on others. payouts reflect the underlying uncertainty, but they vary from pledge to pledge, so the set of equilibrium pledges is inefficient. This bargaining outcome is embedded in a dynamic contribution game, with endogenous technology, participation, enforcement, and contract terms, to investigate when pledge-and-review bargaining is desirable. The model's predictions can rationalize the key differences between the climate agreements signed in Kyoto (1997) and Paris (2015) as well as the development from the former to the latter.
Keywords: 330; dynamic games; bargaining games; Nash program; climate change; Paris Agreement; Kyoto Protocol